Pop art is embodied in contemporary ceramics "An analytical study of ceramic works inspired by consumer culture" (Al-Academy, 2026)
This research investigates the representations of Pop Art in contemporary ceramics, exploring how ceramicists transform banal consumer commodities into conceptual discourse. Utilizing an analytical approach, the study deconstructs Pop Art’s philosophy and its transition from the everyday to artistic production, grounded in "parodic mimesis" and contextual displacement. The findings reveal that contemporary ceramicists do not merely imitate products formally; they exploit the "permanence of clay" to expose the "ephemerality of consumption." Consequently, this representation constitutes a sociological revolution, rendering the ceramic work an open semiotic text that bridges elite art and mass culture, offering a critical vision of capitalist hegemony through the medium of contemporary clay.